The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fvets.2017.00184
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Features of a Salmonella Heidelberg Strain Isolated in Broilers in Brazil and Their Possible Association to Antibiotics and Short-Chain Organic Acids Resistance and Susceptibility

Abstract: Salmonella enterica serovar Heidelberg is a human pathogen also found in broilers. A strain (UFPR1) has been associated with field reports of resistance to short-chain organic acids (SCOA) in broilers in the South of Brazil, but was susceptible to a Bacillus subtilis-based probiotic added in feed in a related study. This work aimed to (i) report clinical symptoms caused by SH UFPR1 in broilers, (ii) study its susceptibility to some antibiotics in vitro, and (iii) SCOA in vivo; and (iv) relate these phenotypic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The environmental persistence of MDR S . Heidelberg in poultry farms may allow for continued exposure and the often asymptomatic infection of live poultry [46, 47]. Another reason that allowed these S .…”
Section: Discussionmentioning
confidence: 99%
“…The environmental persistence of MDR S . Heidelberg in poultry farms may allow for continued exposure and the often asymptomatic infection of live poultry [46, 47]. Another reason that allowed these S .…”
Section: Discussionmentioning
confidence: 99%
“…In some situations, IL-10 could act as a chemoattractant to CD8+ T cells (JINQUAN et al, 1993;XI et al, 2017), activate cytotoxic T cell activity (SANTIN et al, 2000), and increase the maturation of CD8+ T memory cells (LAIDLAW et al, 2015). Shanmugasundaram et al, (2015) and Kogut et al, (2016) have observed that Tregulatory cells increase expression of IL-10 cells after Salmonella infection, which suggests a "tolerogenic" response allowing the bacteria to persist in the lumen. Like the vaccine, this could be a mechanism to inhibit colonization, since maintaining the live vaccine in the lumen could have inhibited colonization after the Salmonella challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The Brazilian SH strain (UFPR1) used in this trial was isolated from commercial broiler carcasses in the south of Brazil. A recent study reported its complete genome associated with high and intermediate resistance against short-chain organic acids and some antibiotics, respectively (SANTIN et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This serovar has also shown AMR to several antibiotics, raising concern among veterinary and public health authorities [69,191,192]. Most S. Heidelberg strains are resistant to tetracycline, nalidixic acid, and ampicillin, as well as some other antimicrobials [49,69,135,[193][194][195][196][197][198] (Table 1). Furthermore, an MDR profile has been common in most isolates [49,135,194,195,197].…”
Section: Salmonella Heidelbergmentioning
confidence: 99%